2012
DOI: 10.2202/1556-3758.2503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Damage to Pinto Bean Seeds as Affected by Moisture Content, Impact Velocity and Seed Orientation

Abstract: The objective of this experiment was evaluate of the impact damage to pinto bean seeds where seed moisture content (9.25, 12.51, 15.01, 17.52, 20.01% wet basis), impact velocity (5.5, 8, 10, 12.5 and 15m/s) and seed orientation (end and side) were independent variables. The study was conducted under laboratory conditions, using an impact damage assessment device. The results showed that impact velocity, moisture content and seed orientation significantly influenced the physical damages of pinto beans at 1% lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
3
10
0
1
Order By: Relevance
“…Previous investigations have found that the moisture content of grain has significant impact on the contact performance of grinding threshing [76][77][78][79][80][81][82] . The higher the moisture content is, the more severe the damage to grain kernels in grinding threshing is.…”
Section: Grinding Threshingmentioning
confidence: 99%
“…Previous investigations have found that the moisture content of grain has significant impact on the contact performance of grinding threshing [76][77][78][79][80][81][82] . The higher the moisture content is, the more severe the damage to grain kernels in grinding threshing is.…”
Section: Grinding Threshingmentioning
confidence: 99%
“…Mechanical injuries can be caused by any type of physical and mechanical action, but injuries caused by the impact of moving parts of machines during harvesting and postharvest processing are the most serious (Shahbazi, 2011 ). The grains of agricultural products are constantly subjected to impact forces from machines from the moment they are harvested to the time they are transferred into storage (Shahbazi et al, 2011a , 2011b ; Shahbazi, Dolwlatshah, & Valizadeh, 2012 ; Shahbazi, Valizadeh, & Dolatshaie, 2012 ). Improper design and performance of machines in each of these stages can cause mechanical damage.…”
Section: Introductionmentioning
confidence: 99%
“…storage (Shahbazi et al, 2011a(Shahbazi et al, , 2011bShahbazi, Dolwlatshah, & Valizadeh, 2012;Shahbazi, Valizadeh, & Dolatshaie, 2012). Improper design and performance of machines in each of these stages can cause mechanical damage.…”
mentioning
confidence: 99%
“…[9] The mechanical response of sunflower seeds to loading has also shown that the moisture content plays an important role in the mechanical properties Gupta and Das. [13] Studies on seeds have also demonstrated that increases in moisture content of rapeseed, wheat, and beans lead to decreased damage during impact Shahbazi, et al, [14] Szwed, and Lukaszuk. [15] In cases where the brittleness of the kernel has increased damage during post-harvest and processing, water conditioning has been used on nuts and grains to reduce kernel mechanical damage Aydin, [6] Davidson Jr, et al, [7] Shahbazi, [9] Shirmohammadi and Fielke, [2] Sims, [10] WoŸniak, [11] Woźniak and Styk.…”
Section: Introductionmentioning
confidence: 99%